Home sweet court? Examining disparities in individual performance between All-NBA and Non-All-NBA players: home versus away games comparison across 23 seasons (1997-2023) - Alonso-Pérez-Chao, E.; Martin-Castellanos, A.; Calleja-González, J.; Portes, R.; Jiménez-Sáiz, S. L. (Perceptual and Motor Skills, 2025)
In this study, we assessed players` technical and tactical performance, based on home or away venues and examined whether these differences varied between All-NBA and Non-All-NBA players. We analyzed data from 23 NBA seasons (1997-1998 to 2022-2023), excluding seasons impacted by lockouts and pandemic restrictions. The dataset, sourced from open-access NBA records, included 243,067 games and variables such as points per game, rebounds (offensive and defensive), shooting percentages (2-points %, 3-points %, free-throw %), assists, steals, blocks, turnovers, personal fouls, and efficiency, normalized per 48 minutes of play. We found significant differences based on venue and player tier. Points per game were higher at home (p < .001) and for All-NBA players (p < .001), with a strong interaction effect showing that All-NBA players performed best at home. Free throw and 2P % were also higher at home and for All-NBA players (both p < .001). Efficiency, assists, and rebounds were higher at home and for All-NBA players, with interaction effects showing that All-NBA players at home excelled over other conditions (all p < .001). Turnovers were higher for All-NBA players at home (p < .001), while steals were lower for Non-All-NBA players in away games. Blocks were highest at home, with Home All-NBA players leading (p < .001). Personal fouls were higher in away games and for Non-All-NBA players (p < .001). We concluded that both venue and player tier were significantly associated with better performance, with home games offering a distinct advantage and All-NBA players showing superior performance to Non-All-NBA Players across most metrics. Practical applications include optimizing recovery and travel schedules to manage away-game challenges, leveraging home-court advantages, and tailoring strategies to maximize elite player performance in different environments.